IDENTIFIKASI TINGKAT KETERAMPILAN SEPAKBOLA SISWA PUTRA KELAS VI DI SDN 2 CIAWILOR - Tris Mulyo Purnomo; Dani Nurdiansyah (Indonesian Journal of Education Teaching and Learning (IJETL), 2025)
This research discusses the problem of the level of football skills of male students at SD Negeri 2 Ciawilor Ciawigebang Kuningan. The aim of this research was to determine the level of football skills of male students at SD Negeri 2 Ciawilor. The population in this study were all male students at SD Negeri 2 Ciawilor, totaling 17 students. The instrument used was a football skills test for 10-12 year olds from Daral Fauzi R. To determine the level of football skills, six test items were used, namely: 1) dribbling the ball, 2) short passes, 3) throw-ins, 4) running with the ball, 5) heading, and 6) shooting at the goal. The data analysis technique used in this research is descriptive statistics. The results of the research showed that none of the male students' football skill level at SD Negeri 2 Ciawilor Ciawigebang Kuningan was in the very good category, 11.76% were in the good category, 64.70% were in the medium category, 17.64% were in the poor category, and 1 child was in the very poor category with a percentage of 5.88%.